Recent advances in black liquor valorization. (April 2022) - Morya, Raj; Kumar, Madan; Tyagi, Isha; Kumar Pandey, Ashutosh; Park, Jungsu; Raj, Tirath; Sirohi, Ranjna; Kumar, Vivek; Kim, Sang-Hyoun
Graphical abstract: Highlights: Black liquor is a prospective lignocellulosic feedstock for circular bioeconomy. Black liquor can be converted into bioplastics, chemicals, hydrogen and methane. Anaerobic digestion would be the keystone process in black liquor valorization. Policy related research is required in the sustainable fuel production. Abstract: Lignocellulosic biomass is projected as a prospective renewable alternative to petroleum for the production of fuel and chemicals. Pretreatment is necessary to disrupt the lignocellulosic structure for extraction of cellulose. Biomass after pretreatment is segregated into cellulose rich solid fraction and black liquor (lignin and hemicelluloses) as a liquid stream. The plant polysaccharide-based industry primarily utilizes the cellulosic fraction as raw material, and carbon rich black liquor discarded as waste or burnt for energy recovery. This review highlights the recent advancements in the biological and chemical valorization of black liquor into fuels and chemicals. The recent research attempted for bioconversion of black liquor into Bioplastic, Biohydrogen, Biogas, and chemicals has been discussed. In addition, the efforts to replace the conventional energy recovery method with the advanced chemical process along with their modifications have been reviewed that will decide the sustainability of the lignocellulosic biomass-based industry.